Image analysis and recognition : 13th International Conference, ICIAR 2016, in memory of Mohamed Kamel, Póvoa de Varzim, Portugal, July 13-15, 2016, proceedings /: 13th International Conference, ICIAR 2016, in memory of Mohamed Kamel, Póvoa de Varzim, Portugal, July 13-15, 2016, proceedings. (2016) - Unknown
No abstract available